2000
DOI: 10.1046/j.1365-2567.2000.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of β‐chemokines and down‐modulation of CCR5 co‐receptors inhibit simian immunodeficiency virus transmission in non‐human primates

Abstract: SUMMARYA non-cognate mechanism of protection against human immunode®ciency virus-1 (HIV-1) infection involves up-regulation of b-chemokines, which bind and may down-modulate the CCR5 co-receptors, thereby preventing transmission of M-tropic HIV-1. The objective of this investigation was to evaluate this mechanism in vivo in non-human primates. Rhesus macaques were immunized by a modi®ed targeted lymph nodes (TLN) route with recombinant simian immunode®ciency virus (SIV) glycoprotein 120 (gp120) and p27 in alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
0
33
1
Order By: Relevance
“…Thus, the beta-chemokine-mediated control of viral replication that occurs in PBMC culture systems in vitro does not seem to play a role in vaccine outcomes. This finding contrasts with those of other studies that have reported an association between in vitro beta-chemokine secretion by CD8 ϩ T cells in PBMC and vaccine-mediated protection against a SIV/SHIV challenge (3,6,7,18,21,24,29,30). The conclusions of these studies were based on in vitro assays using mitogen stimulation.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Thus, the beta-chemokine-mediated control of viral replication that occurs in PBMC culture systems in vitro does not seem to play a role in vaccine outcomes. This finding contrasts with those of other studies that have reported an association between in vitro beta-chemokine secretion by CD8 ϩ T cells in PBMC and vaccine-mediated protection against a SIV/SHIV challenge (3,6,7,18,21,24,29,30). The conclusions of these studies were based on in vitro assays using mitogen stimulation.…”
Section: Discussioncontrasting
confidence: 88%
“…However, live attenuated vaccines have consistently provided the most effective protection against a challenge with virulent SIV and they stimulate a broad range of antiviral immune responses in rhesus macaques (1,21). Many studies have found an association between the in vitro secretion of beta-chemokines by peripheral blood mononuclear cells (PBMC) and vaccine-mediated protection from SIV or SHIV challenge (3,5,24,29,30). However, recent studies have shown that high beta-chemokine levels correlate with the disease progression of SIV and HIV infections (25,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibodies for these flow cytometric determinations have been used repeatedly by our laboratories and the laboratories of others to identify CD4 and CCR5 on the surface of rhesus monkey cells with good sensitivity (2,34,35,48,49,53,55,66). For the present experiments, we used appropriate CD4/CCR5-positive and -negative controls to establish gating and sensitivity.…”
Section: Cd4mentioning
confidence: 99%
“…This mechanism is independent of HIV or SIV priming and thus constitutes noncognate immunity to these viruses. The mechanism of protection involves the three CC chemokines (CCL3, CCL4, and CCL5) which are elicited in vitro and in vivo by the stimulation of human or simian CD4 ϩ T cells and dendritic cells with HSP70 (21,39). These chemokines inhibit preentry HIV-1 binding to CCR5 by the R5 strains of HIV-1 and by most SIV strains (9,24); CCL3 may also inhibit postentry HIV-1 (3).…”
Section: Discussionmentioning
confidence: 99%